BRINE SHRIMP LETHALITY BIOASSAY OF BOUGAINVILLEA GLABRA - Dokuparthi, Sudheer K; Lakshmi, G; Anjana, A; Fatima, Syed F; Ashwini, P; Kandagatla, Suresh; Raj, Suthakaran (Journal of Drug Delivery and Therapeutics, 2018)
The crude methanolic extract of Bougainvillea glabra leaves has been investigated for the evaluation of the cytotoxic activity. All the extracts of the plant were screened for their cytotoxicity by using brine shrimp nauplii (Artemia salina) lethality bioassay. The toxicity was assessed in terms of LC50 (lethality concentration), 10 nauplii were taken into three replicates of each concentration of the methanolic leaf extract. Brine shrimps were checked for the mortality during 24 hrs period, surviving brine shrimps were counted and LC50 was evaluated. The results showed that all the extracts were showing potent toxicity to the nauplii. The LC50 values were compared to the standard potassium dichromate. It indicates that the extracts are toxic even at low doses. Further investigation is needed to study the acute and subacute toxicity of the extracts for its safe application to the humans. Keywords: Artemia salina, cytotoxicity, Bougainvillea glabra, mortality